In vitro antimicrobial profile of Ureaplasma urealyticum from genital tract of childbearing‐aged women in Northern and Southern Italy. Issue 6 (30th September 2013) - Pignanelli, Salvatore; Pulcrano, Giovanna; Iula, Vita Dora; Zaccherini, Patrizia; Testa, Antonio; Catania, Maria Rosaria
<x xml:space="preserve">Abstract</x> Ureaplasma urealyticum is an opportunistic pathogen during pregnancy and in newborns. Other clinical problems related to U. urealyticum infections are: no susceptibility to cell wall‐active drugs, limits of antibiotic treatment in pregnancy, and spread of antimicrobial resistance. In addition, the results of antimicrobial susceptibility against U. urealyticum from various countries are few and controversial. The antimicrobial susceptibility of U. urealyticum, isolated from cervical swabs and collected from outpatient childbearing‐aged women in Italy from 2009 to 2012, was performed against fluoroquinolones, macrolides, streptogramin and tetracyclines, using an available biochemical commercial kit and a specific solid culture medium, to improve the therapeutic management of these pathogenic agents. Ureaplasma urealyticum was detected in 49.4% of samples, but significant bacterial load was revealed in 29.8%. In vitro tetracyclines showed the best activity against U. urealyticum, followed by streptogramin, macrolides, and fluoroquinolones.